Thermo-optical-transmission OC/EC and Raman spectroscopy analyses of flame-generated carbonaceous nanoparticles. (15th February 2022) - Bocchicchio, Serafina; Commodo, Mario; Sgro, Lee Anne; Chiari, Massimo; D'Anna, Andrea; Minutolo, Patrizia
Highlights: Size and carbon content of various kind of nascent soot particles are analyzed. Thermo-optical-transmission (TOT) and Raman spectroscopy (RS) are used. Organic (OC), pyrolytic (PC), and elemental (EC) carbon are compared to RS results. Mass absorption coefficient (MAC) is derived from TOT and is correlated with OC/EC. Abstract: Elemental and organic carbon content of flame-generated soot nanoparticles produced under different operating conditions of equivalence ratio and particle residence time is determined by thermo-optical-transmission measurements, while particle carbon structure is characterized by Raman spectroscopy analysis. The sampled soot nanoparticles are produced in slightly-rich, almost bluish, flames and comprise small 2–4 nm nascent soot nanoparticles, often neglected in the primary carbonaceous emissions from combustion systems, and larger 4–15 nm soot particles. The application of the NIOSH-like protocol for the thermo-optical-transmission analysis allows the separation of the total carbon (TC) into fractions of organic carbon (OC), pyrolytic carbon (PC), and elemental carbon (EC). The lowest amount of elemental carbon is measured in young soot nanoparticles and it is progressively larger in mature soot particles. The organic carbon has the opposite trend and shows that it is the "pyrolyzable" carbon fraction of the young soot nanoparticles that transforms into elemental carbon in the primary soot. Raman spectroscopy showed consistent results as compared to the thermo-optical-transmission analysis indicating a analogous trend in the graphitization order of the different soot particles. Most importantly, the logarithm of the intensity of the measured photoluminescence background shows a linear dependence with the OC/EC ratio. Mass absorption coefficients (MAC) were retrieved by the thermo-optical-transmission analysis for the four soot samples; the estimated MAC coefficient ranged from 2 to 6 m 2 /g, dependently from the relative percentage of EC component. The data are in excellent agreement with currently available literature data and extend the determination of MACs to carbonaceous particles with a larger OC/TC content.